Discharge against medical advice after hospitalisation for acute myocardial infarction. Issue 4 (12th September 2018) - Kwok, Chun Shing; Walsh, Mary Norine; Volgman, Annabelle; Alasnag, Mirvat; Martin, Glen Philip; Barker, Diane; Patwala, Ashish; Bagur, Rodrigo; Fischman, David L; Mamas, Mamas A
Abstract : Background: Discharge against medical advice (AMA) occurs infrequently but is associated with poor outcomes. There are limited descriptions of discharges AMA in national cohorts of patients with acute myocardial infarction (AMI). This study aims to evaluate discharge AMA in AMI and how it affects readmissions. Methods: We conducted a cohort study of patients with AMI in USA in the Nationwide Readmission Database who were admitted between the years 2010 and 2014. Descriptive statistics were presented for variables according to discharge home or AMA. The primary end point was all-cause 30-day unplanned readmissions and their causes. Results: 2663 019 patients were admitted with AMI of which 10.3% (n=162 070) of 1569 325 patients had an unplanned readmission within 30 days. The crude rate of discharge AMA remained stable between 2010 and 2014 at 1.5%. Discharge AMA was an independent predictor of unplanned all-cause readmissions (OR 2.27 95% CI 2.14 to 2.40); patients who discharged AMA had >twofold increased crude rate of readmission for AMI (30.4% vs 13.4%) and higher crude rate of admissions for neuropsychiatric reasons (3.2% vs 1.3%). After adjustment, discharge AMA was associated with increased odds of readmissions for AMI (OR 3.65 95% CI 3.31 to 4.03, p<0.001). We estimate that there are 1420 excess cases of AMI among patients who discharged AMA. Conclusions: Discharge AMA occurs in 1.5% of the population with AMI and these patients are at higher risk of early readmissions for re-infarction. Interventions should be developed to reduce discharge AMA in high-risk groups and initiate interventions to avoid adverse outcomes and readmission.